Hand-assisted laparoscopic donor nephrectomy: a single centre experience - Tomasz Jakimowicz; Michał Macech; Amro Alsharabi; Łukasz Romanowski; Tadeusz Grochowiecki; Dorota Lewandowska; Piotr Kaliciński; Magdalena Durlik; Leszek Pączek; Sławomir Nazarewski (Videosurgery and Other Miniinvasive Techniques)
Introduction : The advantages of a minimally invasive nephrectomy are a faster recovery and better quality of life for the donors. Until recently, the majority of donor nephrectomies in Poland were done by open surgery. Aim : To present a single centre experience in hand-assisted laparoscopic donor nephrectomy (HALDN). Material and methods: The first videoscopic left donor nephrectomy in Poland was performed in our department in 2003 using a hand-assisted retroperitoneal approach. From 2011, we changed the method to a transperitoneal approach and started to harvest also right kidneys. Since then, it has become the method of choice for donor nephrectomy and has been performed in 59 cases. Preoperatively, kidneys were assessed by scintigraphy and by angio-Computed tomography. We harvested 32 left and 27 right kidneys. There were double renal arteries in 2 cases and triple renal arteries in 1 case. The warm ischaemia time (WIT) was 80–420 s (average 176.13 s); operative time was 85–210 min (average 140 min). Results: All procedures were uncomplicated, and all donors were discharged after 2–8 days with normal creatinine levels. The average follow-up period lasted 23 months (1–51 months). Out of all of the cases, 1 case had two minor complications, while all others were uneventful. None of the donors were lost to follow-up. All of the kidneys were transplanted. There were 2 cases of delayed graft function (DGF) and 2 cases of ureter necrosis. One of those kidneys was lost in the third postoperative week. Conclusions : Our limited experience shows that HALDN is a safe method and should be used routinely instead of open surgery.